Wilson & Walker's principles and techniques of Biochemistry and molecular biology - Clokie, Samual (New Delhi : Cambridge University Press, 2023)
It integrates the theories and methods that drive the fields of biology, biotechnology and medicine, comprehensively covering both the techniques students will encounter in lab classes and those that underpin current key advances and discoveries. The contents have been updated to include both traditional and cutting-edge techniques most commonly used in current life science research. Emphasis is placed on understanding the theory behind the techniques, as well as analysis of the resulting data. New chapters cover proteomics, genomics, metabolomics, and bioinformatics, as well as data analysis and visualisation. Using accessible language to describe concepts and methods, and with a wealth of new in-text worked examples to challenge students' understanding, this textbook provides an essential guide to the key techniques used in current bioscience research.
includes index
Keywords: Enzymes and receptors -- Spectroscopic techniques -- Microscopy -- Flow cytometry